Factors Influencing the Formation of Terminology Related to ChatGP - Normamatova Zakhro Dilshodovna (Scientific Trends, 2025)
This article investigates multiple linguistic, technological, interdisciplinary, and social factors influencing the development of terminology associated with ChatGPT. Through qualitative corpus analysis and expert interviews, the research identifies key determinants driving terminological innovation and highlights challenges in standardizing the lexicon within this dynamic domain. The rapid advancement of artificial intelligence (AI) and natural language processing (NLP) technologies, exemplified by models such as ChatGPT, necessitates the continual formation and evolution of specialized terminology.
Keywords: ChatGPT, Terminology Formation, Artificial Intelligence, Natural Language Processing, Terminology Development, Linguistic Innovation, Technological Influence, Interdisciplinary Terminology, Social Dynamics, Terminology Standardization